Peran Organisasi Himpunan Mahasiswa Program Studi Pendidikan Pancasila dan Kewarganegaraan dalam Peningkatan Soft Skill - Muhammad Thoyyib Fuady; Hariyanto Hariyanto; Ahmad Fauzan; Bagdawansyah Alqadri (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2022)
The purpose of this study was to find out 1) the role of the HMPS PPKn FKIP UNRAM organization, 2) Soft Skill improvement of students of the PPKn FKIP UNRAM study program, 3) The role of the HMPS PPKn FKIP UNRAM organization in improving soft skills. This study uses a qualitative approach to the type of survey. The subjects in this study were the chairperson and secretary of the HMPS PPKn FKIP UNRAM 2021. Meanwhile, the informants in this study were the division coordinators related to soft skill development. The informants of this study were determined by purposive sampling technique, namely by using certain considerations so that the data from the informants were not arbitrary. Data was collected by using interview, observation and documentation techniques. Data analysis was carried out using the Miles and Huberman model which consisted of three steps, namely data reduction, data presentation, and drawing conclusions. The results of the study show that (1) the Organization of HMPS PPKn FKIP UNRAM has an important role to students of the PPKn FKIP UNRAM study program seen from the potential development work program carried out at any time according to the division, (2) Improvement of soft skills in the HMPS PPKn FKIP Unram organization, ( 3) The organization of HMPS PPKn FKIP UNRAM has an important role for students in improving soft skills in the Civics study program, it can be seen from the habituation process carried out by work program activities continuously and repeatedly.